(untitled) (Politeja, 2021)
The paper examines the potential for the EU to act as a leading actor in internationalization of higher education area based on the case of India – one of the largest higher education national systems, which has been in a process of massification and transformation. Based on the general framework of strategic cooperation between the EU and India, the paper looks at the EU’s strategies and instruments for cooperation in the area of higher education, considers the current picture and identifies enabling factors for intensification of this cooperation. It raises the question of whether the EU can go beyond bilateral relations between higher education institutions and become a collective driver of higher education cooperation between India and the European Higher Education Area, and what the barriers and challenges in developing the external dimension of the EU’s higher education policy are.